Damage and Fracture of Composite Materials and Structures - Tamin, Mohd Nasir.; Tamin, Mohd Nasir. (Advanced Structured Materials,, 2012)
This monograph presents recent research findings on fracture properties and behavior of the composites, and their damage and cracking process under both quasi-static and impact loading conditions. Theoretical treatment, experimental investigation and numerical simulation aspects of the mechanics of composites, including sandwich structures are included.